Locked patellar dislocation: a case report - Michels Frederick; Pouliart Nicole; Oosterlinck Dirk (Journal of Medical Case Reports, 2008)
Abstract Introduction Acute patellar dislocation is a relatively common problem. The most common dislocation is laterally in the coronal plane. Sometimes spontaneous reduction occurs, but if not, closed reduction can easily be done. In this paper, we report a very uncommon type of locked dislocation which required an open reduction. Case presentation A 16-year-old girl of Hispanic origin sustained a sudden dislocation of the patella while she was dancing. Pre-operative computed tomography revealed a patellar dislocation with rotation around the vertical axis with the patella wedged on the side of the lateral condyle. Closed reduction failed. Open reduction was needed and the torn structures were repaired. At 1-year follow-up, she had a good functional outcome and reported no recurrence of dislocation. Conclusion This case report shows that some patellar dislocations may be irreducible with the closed technique. Computed tomography is valuable in case of doubt. If an open reduction is needed, the medial ligamentous structures should be repaired.